Stream contamination by trace elements: biota incorporation and phytoremediation - Loureiro,Rafael Chaves (2020)
Abstract: In this review, we present information about the presence of trace elements on streams and the consequences related to the increase of these chemical elements on aquatic systems. Although several studies on trace elements contamination in aquatic environments are conducted on point sources, non-point sources also have a high potential to contaminate water bodies. Some trace elements are important for the development of an organism. However, even essential elements, in high concentrations, may be toxic to aquatic organisms. In some cases, trace elements may accumulate and be transferred along food webs, generating changes in the structure and functioning of terrestrial ecosystems. The phytoremediation techniques could be an important tool in reducing the problems generated by trace elements. Thus, understanding the effects generated by the increase of trace elements concentrations on aquatic ecosystems becomes important to help public managers to apply solutions for the mitigation of this chemical pollution on natural resources.